An in vitro study of magnetization transfer and relaxation rates of hematoma. - Gomori, J M; Grossman, R I; Asakura, T; Schnall, M D; Atlas, S; Holland, G; Mittl, R L (American Journal of Neuroradiology, 1993)
PURPOSE To assess, in an in vitro model of acute hematoma, whether hemoglobin immobilization by clot and red cell membrane aging can account for the T2 shortening usually attributed to deoxyhemoglobin.METHODS Clotted and heparinized blood samples were packed (100% hematocrit). The apparent magnetization transfer rate (AMTR), T1 and T2 relaxation rates of the samples, and images with a volunteer's head were obtained at 1.5 T.RESULTS The AMTR and T1 and T2 relaxation rates were unaffected by the presence of clot. The AMTR was unaffected by red cell aging. The diamagnetic packed blood samples, which are much denser than brain, were isointense to gray matter on T2-weighted images and had about one-fifth the AMTR of white matter.CONCLUSIONS Hemoglobin immobilization by clot structure or red cell contraction with aging is insignificant and does not contribute to the T2 shortening of acute hematoma. The low AMTR and T2 relaxation rates of diamagnetic blood appear to be caused by the mobility of hemoglobin and by the red cell's lack of immobile macromolecular structures such as those associated with nucleated brain cells.